Intelligent M2M: Complex event processing for machine-to-machine communication. Issue 3 (15th February 2015) - Bruns, Ralf; Dunkel, Jürgen; Masbruch, Henrik; Stipkovic, Sebastian
Highlights: Event-driven software architecture of decision support systems for M2M is proposed. Complex event processing serves as key technology for intelligent M2M systems. General architecture defines M2M-specific domain, event and state models. Machine data is processed by a CEP event processing pipeline in real-time. It is shown how the architecture can be adapted to real-world M2M scenarios. Abstract: M2M (machine-to-machine) systems use various communication technologies for automatically monitoring and controlling machines. In M2M systems, each machine emits a continuous stream of data records, which must be analyzed in real-time. Intelligent M2M systems should be able to diagnose their actual states and to trigger appropriate actions as soon as critical situations occur. In this paper, we show how complex event processing (CEP) can be used as the key technology for intelligent M2M systems. We provide an event-driven architecture that is adapted to the M2M domain. In particular, we define different models for the M2M domain, M2M machine states and M2M events. Furthermore, we present a general reference architecture defining the main stages of processing machine data. To prove the usefulness of our approach, we consider two real-world examples 'solar power plants' and 'printers', which show how easily the general architecture can be extended to concrete M2M scenarios.